PENGGUNAAN MULTISTAGE FILTER ADAPTIVE WIENER UNTUK MENINGKATKAN KUALITAS CITRA DIGITAL - Utaminingrum, Fitri; Prijono, Wahyu Adi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2007)
One way to enhance the quality of digital image from gaussian noise disturbance is trough a combined Adaptive Filter and Wiener one. This then called the Adaptive Wi-ener Filter is capable of estimating the noise, first by finding the adaptation parameters mean and variance calculated from the noisy image data.The Adaptive Wiener Filter performs better in a multistage scheme, so that higher resulting signal to noise ratio can be achieved. The associated analysis and evaluation is based on the corresponding MSE (Mean Square Error) and PSNR (Peak to Signal Noise Ratio) for comparing with those obtained the comman Median Filter and Average Filter.With two representative digital images used, which are black and white and color, respec-tively, the results show significant of MSE of 0.0029562 and 0.0010456 for low noise of variance 0.001, 0.0093262 and 0.0022968 for higher noise of variance 0,035 and in-crement of PSNR of 73.4235 and 77.9335 for the same low noise and of 68.4338 and 74.5195 the same higher noise, due to the multistaging scheme.